A simplified approach to assess the technical prefeasibility of multistory wood-frame buildings in high seismic zones. (15th April 2022) - Berwart, Sebastián; Estrella, Xavier; Montaño, Jairo; Santa-María, Hernán; Almazán, José Luis; Guindos, Pablo
Highlights: Methodology to evaluate the prefeasibility of multistory wood-frame buildings. Developed by analyzing 201 case studies in high seismic zones. Global stiffness and inter-story deformations can be computed with an error less than 11%. Fundamental periods and wall pre-designs can be also estimated. Abstract: Timber structures present a promising solution to reduce the current environmental footprint of the construction industry. For timber buildings designed in seismic zones, wood-frame shear walls are a common lateral resistant system for low- and mid-rise structures. However, for practitioners and engineers unfamiliar with seismic analysis methods for wood-frame structures, estimation of the systems viability can be complex and time-consuming, hindering an extended adoption of timber structures. Therefore, this paper presents a novel methodology to determine at early design phases the technical feasibility of wood-frame structures in highly seismic zones, so-called Simplified Tool for Technical Pre-feasibility or STTP framework. The methodology was developed by analyzing a comprehensive database of 201 wood-frame buildings designed with different seismic performance factors, architectural configurations, number of stories, soil conditions, and anchorage system. By employing input data readily available at the initial stages of structural projects, the proposed methodology verifies the viability of employing wood-frame shear walls as the lateral resistant system of the structure, and provides additional valuable information such as fundamental periods and wall predesigns. Besides, global stiffness and inter-story deformations can be estimated with an error less than 11%. In this way, accurate feedback can be promptly obtained by employing a minimum amount of resources. The results from the methodology can be employed along with cost calculation methods so as to estimate the economic impact of the project and different solutions.